2018
DOI: 10.1177/1010539518786521
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Work-Related Factors on Work Ability Among Young Cambodian Migrant Workers in Thailand

Abstract: This cross-sectional study was conducted to evaluate the effects of work-related factors on work ability among young Cambodian migrant workers in Thailand. The participants consisted of 258 Cambodian migrant workers working in farms in the northeast region of Thailand. Work-related factors consisted of a general work environment and a psychosocial factor. General work environment was assessed by perception of subjects on biological, chemical, physical, and ergonomic factors. The psychosocial factor was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The psychosocial factors were also included in this study. These factors were selected because they are relevant to WAI from a previous study [6,8,[16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychosocial factors were also included in this study. These factors were selected because they are relevant to WAI from a previous study [6,8,[16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…Other factors such as lifestyle (e.g., leisure-time physical activity, diet, smoking and sleep) [13][14][15] and work environment (i.e., chemical hazards, psychological and ergonomics) [16] may also affect WA. Previous studies found that those hazards lead to health problems, including cardiovascular disorder, stress, mental health, respiratory symptoms, musculoskeletal disorder, and accidents [6,8,[17][18][19][20]. Thus, balancing work ability and work demand is a concern due to health effects, work capability and quality of life [16].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted among different populations to reveal the relation between individual and work-related factors with WAI, but it has yet to be used among formal and informal ageing workers in Thailand [12][13][14]. The difference of socio-economic and work-related factors, and the health status and WAI have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…8 A study conducted in Northeast Thailand in 2018 revealed that not only the working environment, but also the psychosocial factors influenced the ability of work, among Cambodian migrant workers (n = 258). 9 In addition, psychological stressors, such as perceived job insecurity, or a lower job satisfaction, do have an impact on the mental well-being of the migrant workers. 10 A hospital-based study was conducted in Malaysia in 1998 to identify the prevalence of psychiatric disorders among the patients from the Association of Southeast Asian Nations (ASEAN) migrants.…”
Section: Introductionmentioning
confidence: 99%